Chapter "Conosci te stesso": o quello che i progettisti possono imparare dalle scienze biologiche contemporanee - Mallgrave, Harry Francis (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2021)
Wherein resides the 'art' in the 'art of building'? Throughout history, architects have generally viewed their field as a craft informed by the human body, a creative sense of play, and technical science. Theory in the second half of the 20 th century departed from this direction by reducing art to the visual and semiotic understanding of form. The remarkable discoveries of the biological sciences in recent decades have opened an entirely new perspective for designers, based on our profound insights into human soci-ality, empathy, emotion, mirror systems, and design's inherent powers of "tactility and kinesis." The dictum "know thyself," once inscribed in stone at the entrance of the Temple of Apollo at Delphi, in many ways holds the key to locating the missing 'art' of design.